Range‐edge populations of seaweeds show niche unfilling and poor adaptation to increased temperatures. (3rd February 2023) - Hernández, Sandra; García, Ana G.; Arenas, Francisco; Escribano, M. Pilar; Jueterbock, Alexander; De Clerck, Olivier; Maggs, Christine A.; Franco, João N.; Martínez, Brezo D. C.
Abstract: Aim: Global warming is affecting the distribution of species worldwide, but the level of adaptation of edge populations to warmer temperatures remains an open question. Here, we assess the thermal tolerance of populations of two habitat‐forming seaweeds along their latitudinal range, using thermal niche unfilling to assess their resilience to global warming. Location: European Atlantic coastline. Taxon: Ascophyllum nodosum (Linnaeus) Le Jolis (Phaeophyceae) and Chondrus crispus Stackhouse (Rhodophyta). Methods: We studied the ecotypic variation in upper survival temperatures (USTs) by measuring survival and growth of adults representing populations under a gradient of seawater temperature (12–30°C). Comparing the USTs with maximum seawater temperatures obtained from satellites, we investigated safety margins and niche unfilling states, both in recent history and under future climate scenarios. Results: USTs (≈24°C) did not differ significantly between populations, except for higher values (27.9°C) for the northernmost populations (cold edge) of A . nodosum . Populations of both species had thermal safety margins over the last few decades (from 1982 to 2021). However, projections based on USTs showed that in several years these margins have been eliminated and will completely disappear in the Bay of Biscay under RCP4.5 and RCP6.0 2090–2100 IPCC scenarios for C . crispus and under RCP8.5 for both species, threatening the populations there. Main Conclusions: Southern marginal populations were not better adapted to global warming than populations elsewhere. Both seaweed species tolerated higher temperatures than the ambient maxima, suggesting a thermal niche unfilling state with thermal safety margins in their recent history. However, those are being depleted by ongoing climate change and this trend is predicted to increase. Marine heat waves are important threats to these habitat‐forming species, transiently reducing or even eliminating safety margins in the hottest parts of the European Atlantic coastline, contributing to explaining the distributional gap there.